Los líquidos iónicos a temperatura ambiente (RTILs): Propiedades, aplicaciones y perspectivas futuras - Kong Moreno, Maynard (2009)
Room temperature ionic liquids (RTILs): Properties, applieations and future prospeetsResearch and development of room-temperatureionic I iquids (RTILs) is becoming more important, as a need to count with materials and chemical substances suitable for several processes in chemical industries, as well as for the growing use of alternative sources of energy, much more friendly with our environment. In this paper is presented a review on ionic liquids, their physical and transport properties, current and future applications